Natureza e participação social, uma nova estética para o Desenho Urbano - Leite, Maria Angela Faggin Pereira (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1993)
The shape of the landscape is the result of the balance between several temporal and spacial forces and processes. In away, landscape is reflex of the social view of the productive system and changes whenever theories, philosophic principles or the needs for its existence are not real or evident anymore. So, its seems natural that Landscape Architecture goes naturally through transformations or changes both in relation to its theoretical framework and its praxis. Among these changes the question related to a new way of projectual praxis and aesthetic criteria asks for a deeper discussion